How we developed a trainee-led book group as a supplementary education tool for psychiatric training in the 21st century. (2nd September 2015) - Kan, Carol; Harrison, Simon; Robinson, Benjamin; Barnes, Anna; Chisolm, Margaret S.; Conlan, Lisa
Abstract: Background : Postgraduate medical education has, in recent years, become a dynamic field with the increasing availability of innovative and interactive teaching techniques. Anecdotal evidence suggests that the current focus of psychiatric training on the acquisition of scientific and clinical knowledge is inadequate to address the multidimensional nature of psychiatry. Supplementary teaching tools may be usefully applied to address this need. Methods : A group of trainees at the Maudsley Hospital and Institute of Psychiatry (UK) pioneered the use of a book group as an innovative teaching tool to enhance the psychiatric training experience by, amongst other aspects, facilitating dialogue between peers on fundamental epistemological issues raised by critical engagement with seminal psychiatric texts. Results : Feedback from members suggested that participation in the book group broadened the overall learning potential and experience of psychiatry. The key ingredients were identified as: (i) collaborative peer-to-peer learning; (ii) the use of 'flipped classroom' model; and (iii) joint ownership. Conclusion : The book group has demonstrated real potential to facilitate direct trainee engagement with the multi-faceted nature of psychiatry as a complex humanistic discipline within an informal learning space.